2009
DOI: 10.1089/hum.2008.205
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antitumor Effect of Interleukin-24 Gene in the Survivin Promoter and Retinoblastoma Double-Regulated Oncolytic Adenovirus

Abstract: Interleukin (IL)-24 is an excellent therapeutic gene for cancer therapy. In this work, IL-24 was inserted into Ad.sp-E1A(Delta24), an oncolytic adenovirus with a 24-bp deletion in the E1A gene, which was driven by the survivin promoter to form Ad.sp-E1A(Delta24)-IL-24. Ad.sp-E1A(Delta24)-IL-24 has an excellent antitumor effect in vitro for human nasopharyngeal, liver, lung, and cervical carcinoma cell lines but does no or little damage to normal cell lines L-02 and WI38. Furthermore, it achieved nearly complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Many members of our laboratory have shown the strong anti-tumor effect of the CTGVT strategy. 3,15,16 In this study, the tumor necrosis factor-related apoptosisinducing ligand (TRAIL) gene was incorporated into the oncolytic adenoviral vector AdÁAFPÁD55. TRAIL was first identified and cloned by Wiley et al in 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Many members of our laboratory have shown the strong anti-tumor effect of the CTGVT strategy. 3,15,16 In this study, the tumor necrosis factor-related apoptosisinducing ligand (TRAIL) gene was incorporated into the oncolytic adenoviral vector AdÁAFPÁD55. TRAIL was first identified and cloned by Wiley et al in 1995.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy combines the advantages of both gene therapy and virotherapy by using an oncolytic adenoviral vector (OA) harboring an anti-cancer gene. Currently, two main strategies are applied to construct the viral vector with oncolytic ability, which can specifically infect tumor cells but rarely infects normal cells [3] . The first strategy is to delete the adenoviral genes that are necessary for viral replication in normal cells but not in tumor cells.…”
mentioning
confidence: 99%
“…The second strategy involves transcription targeting through the use of tumor-or tissue-selective promoters, which can control the expression of early viral genes such as E1A and/or E1B that are essential for replication. Our previous studies have shown that CTGVT exhibits greater antitumor effects than gene therapy or virotherapy alone [3,5,6] . The tumor suppressor in lung cancer-1 (TSLC1) was originally identified as a putative tumor suppressor for non-smallcell lung cancer (NSCLC) and was the first named tumor suppressor in lung cancer [7] .…”
mentioning
confidence: 99%
See 2 more Smart Citations